Potential role of fenugreek (Trigonella foenumgraecum) in the prevention of skin aging - Shannaz Nadia Yusharyahya (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Skin aging is a process influenced by several factors, including estrogen.Estrogen modulates the physiology of the skin, and its deficiency inpostmenopausal women accelerates skin aging. Administration of estrogencan delay the skin aging process. Phytoestrogens are estrogen-like compoundsderived from plants that administered via oral as well astopical routes.Trigonella foenum-graecum, commonly known as fenugreek, is one plantscontaining phytoestrogens. Several studies have been conducted on thephytoestregonic activity of fenugreek. Fenugreek extract exhibits estrogenicactivity, as observed in the study of mouse and rat reproductive organs.Fenugreek exhibits estrogenic activity in the reproductive organs of a rat, aswell as demonstrates positive effects on the skin by topical administration.This review explored the fenugreek as the source of phytoestrogens and itsrole in delaying skin aging.